Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Solve for [tex]m[/tex]:

[tex]\[ 5 + 2m = 3 + m \][/tex]

[tex]\[ m = [?] \][/tex]


Sagot :

To solve for \( m \) in the equation \( 5 + 2m = 3 + m \), follow these steps:

1. Move all terms involving \( m \) to one side of the equation and constants to the other side:
- Subtract \( m \) from both sides of the equation:
[tex]\[ 5 + 2m - m = 3 + m - m \][/tex]
- This simplifies to:
[tex]\[ 5 + m = 3 \][/tex]

2. Isolate \( m \) on one side of the equation:
- Subtract 5 from both sides of the equation:
[tex]\[ m = 3 - 5 \][/tex]
- This simplifies to:
[tex]\[ m = -2 \][/tex]

Thus, the solution to the equation is [tex]\( m = -2 \)[/tex].